User's Social Network Site Loyalty - Han, Bo (International Journal of Virtual Communities and Social Networking, 2017)
The answers to the question of how to build a user's loyalty have become the most desirable knowledge to academics and practitioners, when the competitions turn drastic among social network sites. This article proposes a new model to investigate the influential factors of the user's cognitive loyalty and affective loyalty to a social network site. The authors find that the user's actualization of hoped for self and the informativeness of a social network site both have significant positive effects on the user's perceived usefulness and perceived enjoyment, thereby positively influencing the user's loyalties to the Web site.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9panZjc24uMjAxNzA3MDEwMQ